Single-cycle, pseudotyped reporter influenza virus to facilitate evaluation of treatment strategies for avian influenza, Ebola and other highly infectious diseases in vivo - Tan, Tiong Kit; Rijal, Pramila; Huang, Kuan-Ying A.; Hyde, Stephen C.; Gill, Deborah R.; Townsend, Alain R. (Frontiers in Immunology, 2025)
The rapid spread of infectious diseases presents a significant global threat, with seasonal influenza viruses, leading to 290,000–650,000 deaths annually. Emerging high pathogenic influenza strains from animals such as H5N1 and H7N9 further exacerbates pandemic risks. While developing effective vaccines and therapeutics is critical, the evaluation of these interventions is constrained by the requirement for high biosafety containment facilities. To circumvent these challenges, we developed S-Lux, a replication-deficient, single-cycle recombinant influenza virus expressing firefly luciferase (Flux) as a reporter protein. S-Lux can be pseudotyped with haemagglutinin from avian influenza, H5 and H7, enabling real-time monitoring of viral infection in vivo, and facilitate therapeutic antibody evaluation in low-containment facilities. In mice, S-Lux infection resulted in dose-dependent bioluminescent expression in the mouse airways and allowed evaluation of neutralising monoclonal antibodies and clearance of infected cells in mice. To extend this system, we generated ES-Lux by pseudotyping with the Ebola Glycoprotein (GP) and demonstrated that ES-Lux can be used to evaluate the efficacy of Ebola GP-targeting antibodies in vivo. Together, S-Lux and ES-Lux enable robust, simple and time-efficient assessment of antiviral therapy targeting influenza and Ebola virus in vivo, overcoming biosafety constraints that limit traditional efficacy studies.